Synthesis and characterization of biofunctional quaternized xylan-Fe2O3 core/shell nanocomposites and modification with polylysine and folic acid. (1st November 2018) - Ma, Jiliang; Li, Dan; Zhong, Linxin; Du, Fan; Tan, Jiewen; Yang, Jie; Peng, Xinwen
Graphical abstract: Synthesis and characterization of biofunctional quaternized xylan-Fe2O3 core/shell nanocomposites and modification with polylysine and folic acid. Highlights: QX-Fe2 O3 nanocomposites were obtained from xylans and biocompatible γ-Fe2 O3 . QX-Fe2 O3 nanocomposites can be further functionalized with folic acid or polylysine. FA-QX-Fe2 O3 showed excellent performance in T2 -weighted Magnetic Resonance imaging. This study of high-value utilization of xylan has a certain reference value. Abstract: The aims of this study are to prepare quaternized xylan-Fe2 O3 (QX-Fe2 O3 ) core/shell nanocomposites and explore their potential application in the biomedical fields. γ-Fe2 O3 nanoparticles synthesized by a facile solvothermal process are coated with QX via reverse microemulsion method and further modified by polylysine (PLL) and folic acid (FA) to prepare PLL-QX-Fe2 O3 and FA-QX-Fe2 O3 nanoparticles. An obvious strong absorption of γ-Fe2 O3 at 580 cm −1 in the spectra of QX-Fe2 O3 is observed, the Fe element content of QX-Fe2 O3 is 30–75 μg/mL and the saturation magnetization of QX-Fe2 O3 nanoparticles is 1.49 emu/g. The γ-Fe2 O3 and QX-Fe2 O3 nanoparticles are of regular sphericity with diameter of 50–100 nm and 60–150 nm, respectively. The highest zeta potential of QX-Fe2 O3 nanoparticles is −41 mV, and the PLL-QX-Fe2 O3 nanoparticles have a positive potential with a maximum value of 45.2 mV. In addition, FA-QX-Fe2 O3 showed excellent performance in T2 -weighted Magnetic Resonance (MR) imaging with an r2 value of 190 mM −1 S −1 . Each nanocomposite has its own inherent properties, which contributes to its versatile utilization and application potential.